The Nutrition and Health Communication Education Program and For Accurate Science Project of Sabri Ulker Foundation: Initiatives from Turkey - Mutus, Begum; Erdin, Sinem; Sen, Nilufer; Arca, Deniz Miray; Hacaloglu, Selen; Besler, Halit Tanju (Karger, 2020)
In recent decades interest in food and health issues has not ceased to increase globally. Consumers typically obtain information on issues related to food, nutrition, and health via a wide variety of media channels, including TV, radio, newspapers, internet, and social media. Unfortunately, the messages that reach consumers through these different channels can be conflicting, inaccurate, or confusing. The For Accurate Science Platform of the Sabri Ulker Food Research Foundation aims to disseminate current and reliable information to the public about health and nutrition. Since 2017, the Sabri Ulker Food Research Foundation has also organized a 2-day education program, entitled the Nutrition and Health Education Program, with the aim of educating and providing a better understanding of nutrition science and science communication to participants from the media and influencers who are interested in area of nutrition and health. This program is also accredited by the Society of Nutrition and Food Science (SNFS) as an international nutrition communication training program. This year the theme of the program was Popular Diets: Health Effects and Effective Communication. Popular diets is one of the most frequent topics in nutrition communication, sought by millions of people, and where the available information is not always evidence based. A recent meta-analysis by the British Medical Journal on the role of food in weight management found that no dietary method has been shown to achieve superior results in terms of long-term weight maintenance. Many popular diets limit food groups and/or nutrients to achieve faster results. However, these limitations might cause vitamin and mineral deficiencies and lead to hidden hunger in the short and long term. Thus, inaccurate and non-scientific news about popular diets can negatively affect the worldwide burden of hidden hunger. (C) 2020 S. Karger AG, Basel
4th International Congress on Hidden Hunger and the Transformation of Food Systems - How to Combat the Double Burden of Malnutrition? -- FEB 27-MAR 01, 2019 -- Stuttgart, GERMANY
Keywords: Media